Ta có : 99 - 97 + 95 - 93 + 91 - 89 + .... + 3 - 1
= ( 99 - 97 ) + ( 95 - 93 ) + ( 91 - 89 ) + ... + ( 7 - 5 ) + ( 3 - 1 )
= 2 + 2 + 2 + .... + 2 + 2
= 2 x 25
= 50
Ta có : 99 - 97 + 95 - 93 + 91 - 89 + .... + 3 - 1
= ( 99 - 97 ) + ( 95 - 93 ) + ( 91 - 89 ) + ... + ( 7 - 5 ) + ( 3 - 1 )
= 2 + 2 + 2 + .... + 2 + 2
= 2 x 25
= 50
Kết quả phép tính 99 – 97 + 95 – 93 + 91 – 89 + ... + 7 – 5 + 3 – 1 là
Kết quả phép tính 99 – 97 + 95 – 93 + 91 – 89 + ... + 7 – 5 + 3 – 1 là
Kết quả phép tính 99 – 97 + 95 – 93 + 91 – 89 + ... + 7 – 5 + 3 – 1 là
Kết quả phép tính 99 – 97 + 95 – 93 + 91 – 89 + ... + 7 – 5 + 3 – 1 là
Kết quả phép tính 99 – 97 + 95 – 93 + 91 – 89 + ... + 7 – 5 + 3 – 1 là
Kết quả phép tính 99 – 97 + 95 – 93 + 91 – 89 + ... + 7 – 5 + 3 – 1 là
Kết quả phép tính 99 – 97 + 95 – 93 + 91 – 89 + ... + 7 – 5 + 3 – 1 là
Kết quả phép tính 99 – 97 + 95 – 93 + 91 – 89 + ... + 7 – 5 + 3 – 1 là
Kết quả phép tính 99 – 97 + 95 – 93 + 91 – 89 + ... + 7 – 5 + 3 – 1 là